2017
DOI: 10.1016/j.addr.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Proton therapy – Present and future

Abstract: In principle, proton therapy offers a substantial clinical advantage over the conventional photon therapy. This is because of the unique depth-dose characteristics of protons, which can be exploited to achieve significant reductions in normal tissue doses proximal and distal to the target volume. These may, in turn, allow escalation of tumor doses, greater sparing of normal tissues, thus potentially improving local control and survival while at the same time reducing toxicity and improving quality of life. Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
274
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(283 citation statements)
references
References 73 publications
1
274
0
8
Order By: Relevance
“…IMPT can reduce the rectal dose relative to PSPT in the absence of spacers [10], as we observed for V60 and V70 in this study. These reductions may be attributed to more precise dose deposition achieved with IMPT, which allows avoidance of normal structures with complex, curved geometries such as the seminal vesicles; IMPT also uses a ''layer-by-layer'' approach to deliver radiation to a target volume [23]. In the present study, including the seminal vesicles in the CTV contributed to the rectal doses being higher in the PSPT-without-spacer plans.…”
Section: Discussionmentioning
confidence: 72%
“…IMPT can reduce the rectal dose relative to PSPT in the absence of spacers [10], as we observed for V60 and V70 in this study. These reductions may be attributed to more precise dose deposition achieved with IMPT, which allows avoidance of normal structures with complex, curved geometries such as the seminal vesicles; IMPT also uses a ''layer-by-layer'' approach to deliver radiation to a target volume [23]. In the present study, including the seminal vesicles in the CTV contributed to the rectal doses being higher in the PSPT-without-spacer plans.…”
Section: Discussionmentioning
confidence: 72%
“…There is also uncertainty in the physical properties of protons for changes in density and volumes that could affect dose delivery [12]. Lateral scatter is also a concern, although the integral dose is lower [2]. Taken together, it is worth considering the possibility of reporting bias with toxicity rates tracked more carefully for newer technologies.…”
Section: Discussionmentioning
confidence: 99%
“…A study by van der Laan et al [1] found that patients treated with intensity-modulated proton therapy had decreased dose to the pharyngeal constrictors, resulting in decreased rates of dysphagia compared with IMRT. Furthermore, several comparison studies [2][3][4][5] have shown lower energy delivered to regions outside the target and, thus, lower integral dose with proton therapy.…”
Section: Introductionmentioning
confidence: 99%
“…This is not a novelty and it has been discussed and demonstrated in silico since the first studies in the early 2000s [28][29][30]. However, the actual clinical use of PT for the treatment of the whole breast is gaining momentum thanks to the recent gradual spread of proton therapy centers and to the increasing use of PBS techniques and optimized IMPT [31][32][33]. There are at least eight clinical trials currently investigating the use of proton therapy for the treatment of the whole breast with or without nodal irradiation [34].…”
Section: Discussionmentioning
confidence: 99%